The Urgency of Resolving Indonesian Migrant Worker Cases through Restorative Justice Originated to The National Criminal Code - Hevben (Greenation Publisher & Yayasan Global Resarch National, 2025)
Indonesia has the fourth largest population in the world. With such a large population, some of the population seeks work abroad because the number of jobs in the country is inadequate. However, finding a job is not as smooth as imagined , but many of them become conflicts. Based on statistical data from the Ministry of Foreign Affairs, it was revealed that in the period from 2020 to March 2024, at least 3,703 Indonesian citizens (WNI) became victims of Online Scamming crimes, where around 40 percent of them were identified as victims of Human Trafficking (TPPO). Meanwhile, based on data from the Criminal Investigation Unit of the National Police Headquarters, throughout 2023, the Indonesian National Police (Polri) has handled 1,061 TPPO cases with a total of 3,363 victims. However, on the other hand, many Indonesian Migrant Workers who work abroad through placement agents need a solution that is felt to be humane to the victims. With the existence of Law No. 18 of 2017 concerning the Protection of Migrant Workers, there is no protection that can be directly felt by victims who directly feel the losses they experience. In Article 85 (a) Jo. Article 71 a which is only oriented towards punishment and fines for perpetrators of criminal acts whose benefits cannot be felt by the victim. Therefore, there needs to be a more effective solution through Restorative Justice, namely a solution that involves all parties, both the perpetrator, the victim and also the state as a forum to facilitate the agreed settlement so that the victim can feel direct and fast recovery from the perpetrator and by involving the state as a forum that bridges it so that if the Restorative settlement is not resolved by the parties, it can be prosecuted as a last resort. That the purpose of this study suggests a resolution of the conflict between labor supply agencies/corporations and victims of Indonesian Migrant Workers abroad based on Restorative Justice so that the impact of recovery can be felt directly by the victim. In this study, the researcher used the Empirical Juridical method, Juridical which was taken from library materials, legislation, written articles, both journals and articles related to Indonesian migrant workers. From an empirical perspective, the researcher took the researcher's experience in handling Indonesian migrant worker cases and interviews with senior prosecutors who had handled Indonesian Migrant Worker cases.